QSAR STUDY ON 3-SUBSTITUTED INDOLE DERIVATIVES AS ANTI-INFLAMMATORY AGENTS - ASHOK S. NARUTE; MAYURA A. KALE; TUKARAM M. KALYANKAR (International Journal of Pharma and Bio Sciences, 2013)
Anti-inflammatory agents have attracted much attention in recent years in the design of non-steroidal anti-inflammatory agents (NSAIDs), which are devoid of the common side effects of classical NSAIDs. QSAR studies have been performed on a series of 3-substituted indole derivatives with a hope to design compounds with better anti-inflammatory activity and lesser side effects. Various physicochemical parameters were calculated and good predictive QSAR models were generated for anti-inflammatory activity using stepwise multiple regression analysis. Statistically significant models were obtained that gave r-value (correlation coefficient) as <0.80 which depicts a good correlation between anti-inflammatory activity with physicochemical properties, connectivity and conformation of molecule. The indicator variables like presence of aromatic ring and lipophilic groups play an important role in anti-inflammatory activity. Cross validation was performed using the leave one-out method. The results obtained along with validated models bring important structural insight in designing novel 3-substituted indole derivatives as anti-inflammatory agents.